2000
DOI: 10.1055/s-2000-6325
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dibenzo[c,h][1,6]naphthyridine, [2]Benzopyrano[4,3-c]quinoline and Benzo[i]phenanthridine Analogues of the Quaternary Benzo[c]phenanthridines

Abstract: Three concise syntheses of the dibenzo[c,h][1,6]naphthyridines, [2]benzopyrano [4,3-c]quinolines and the benzo[i]phenanthridines are reported. All methods involve Vilsmeier chemistry, either to generate a 12-methyl-6-oxo-6H-[2]benzopyrano[4,3-c]quinolinium salt which after hydrolysis with either ammonia or methanol can ultimately be cyclised to the first two target compounds, whereas the latter can be prepared in one step from 2-(1-pyrrolidino)-3,4-dihydronaphthalene and N-methylformanilide in phosphorus oxych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, the synthesis of monoazachrysene derivatives is uncommon in the literature, except for 2-azachrysene [47,[51][52][53][54], 5-azachrysene [51,[54][55][56][57][58], and 6-azachrysene [51,54,[59][60][61][62][63]. Although 10bazachrysenes are significantly less prevalent, Pshenichnyi et al [64], Mikhalchuk et al [65], and Gulyakevich et al [66] reported substantial advances in this field.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the synthesis of monoazachrysene derivatives is uncommon in the literature, except for 2-azachrysene [47,[51][52][53][54], 5-azachrysene [51,[54][55][56][57][58], and 6-azachrysene [51,54,[59][60][61][62][63]. Although 10bazachrysenes are significantly less prevalent, Pshenichnyi et al [64], Mikhalchuk et al [65], and Gulyakevich et al [66] reported substantial advances in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, some dibenzonaphthyridines, that is, quinoline dimers, act as selective 3‐phosphoinositide‐dependent kinase‐I inhibitors . Many reports represent the synthesis of functionalized naphthyridine derivatives , linear dibenzonaphthridines , and angular dibenzonaphthridines , and only very few accomplish their construction through anilinoquinolines .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Among the quinoline derivatives, pyrido fused quinolines (benzonaphthyridines) and quinoline fused quinolines (dibenzonaphthyridines) play an important role in living cells and in pharmaceuticals. Many reports represent the synthesis of linear 7,8 and angular dibenzonaphthridines [9][10][11] and only very few accomplish their construction through anilinoquinolines. 12,13 Marine sponges are proving to be productive sources of many interesting biologically active nitrogen-containing heterocyclic compounds, including a series of 1H-benzo[de] [1,6]naphthyridine alkaloids.…”
Section: Introductionmentioning
confidence: 99%